Microstructure characterizations of thiol functionalized silica pseudo-nanospheres (SH-SiO2) nanostructured for advanced corrosion protection materials - Biyamin S.A.; Misran H.; Razak I.I.A.; Ramli R.; Othman S.Z.; Azmin A.N.; Peng N.G.; Salim M.A.; Matsumoto A.; Amin N. (Microscopy Society of Malaysia, 2023)
In this study, the silica pseudo-nanospheres materials at ca. 500 nm were functionalized with thiol (SH) using non-surfactant surface modification method. Palm oil derived fatty alcohols (PODFA) was used as green and sustainable surface modifier. The surface modification method successfully attached thiol functional groups in a surfactant-likemanner to produce thiol-silica (SH-SiO2) pseudo-nanospheres. Thereafter, the resulting powder was turned into gel and spin-coated on mild carbon steel at several speeds for corrosion protection applications by exposing the surfaces to more than 36 months of exposure in ambient laboratory condition. Structural characterizations were done on the new surface and exposed surface. The surface microstructure after exposure exhibited less area coated with SH-SiO2 pseudo-nanospheres particles compared with before exposure. Furthermore, elemental analyses results exhibited significant reduction of Si element over time of exposure at ca.70% while the X-ray diffraction analyses results exhibited no phase changes of the mild steel surfaces after 36 months of expo-sure. Visual inspection (VI) suggested that the coated mild steel surfaces were in good condition with no observable rust formation. Therefore, the results obtained in this study suggested that SiO2 spheres functionalization with green and renewable surface modifier are promising candidates of low-cost coating alternatives for corrosion protection of commonly used mild steel. Malaysian Journal of Microscopy (2020). All rights reserved.